From commodity-based value chains to biomass-based value webs: The case of sugarcane in Brazil's bioeconomy. (20th January 2018) - Scheiterle, Lilli; Ulmer, Alina; Birner, Regina; Pyka, Andreas
Abstract: The shift from a fossil-based to a bio-based economy (bioeconomy) requires more efficient utilization of the biomass generated from agricultural production. This can be achieved through the cascading use of biomass, which also offers the potential of creating additional value from biomass by developing novel products. Taking sugarcane as a case study example, this paper aims to analyze how well Brazil, the world's leader in sugarcane production, is positioned to reach these goals. The paper combines two conceptual tools: one is the 'biomass-based value web', which was developed as an extension of the value chain concept with the aim to capture the links within and between value chains that arise from the cascading and joined use of biomass. The other concept is that of the 'national innovation system' (NIS), which serves to identify the different types of actors involved in the biomass value web and the linkages between them. For empirical data collection, the study combined three methods: a mapping of the physical biomass flows in the value web, in-depth interviews with the actors involved, and the application of the 'Net-Map' tool to identify the actors in the NIS and their linkages. The findings show that the development of Brazil's international competitiveness in sugar and ethanol was based on political incentives that resulted in a strong network of institutions that focused on these two products. However, to become a front-runner in the future bioeconomy, the existing innovation network needs to be expanded. In particular, it is important to integrate national and international private sector organizations. The findings also suggest that industries need stronger incentives to collaborate with knowledge institutions. Long-term consistent policies and funding opportunities for risky investments are also required to further strengthen Brazil's innovation network to meet future opportunities and challenges of the bioeconomy.